If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-7x + 9) = -162 Reorder the terms: 3(9 + -7x) = -162 (9 * 3 + -7x * 3) = -162 (27 + -21x) = -162 Solving 27 + -21x = -162 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + -21x = -162 + -27 Combine like terms: 27 + -27 = 0 0 + -21x = -162 + -27 -21x = -162 + -27 Combine like terms: -162 + -27 = -189 -21x = -189 Divide each side by '-21'. x = 9 Simplifying x = 9
| -8+62=-2x-112 | | f(x)=logx | | 2.2/4=1 | | 2x^2=2x+2 | | -2(x+7)+4x=4(x-9) | | a-7=3a+1 | | 96=2n-5(2n-8) | | 3(8y-2)=3(4+2y) | | x^3=12x-5x^2 | | c=4c-12 | | x^2+2.5x+1.5=0 | | -80x^2+320-10=0 | | 18d^2+27d+4=0 | | 80-3x=10-10x | | 12-5x/4=1 | | 12=7-y | | 12=7-9 | | 3x+10=-44-6 | | 7f(f+1)= | | 19/x=12 | | 44-10y=10 | | (2x)+2=6 | | -x-8=-2x+0 | | 6+4x=9+x | | 13.28-2.9m=-17.54-7.5m | | 12+2g=24 | | 4r-22r=22 | | -16.85-5.2g=-13.7g+18.43+16.9g | | 7x-15=-41 | | 1+18v=19+19v | | 2(x)-5=31 | | 3-2x=2(1-x) |